Causes and Consequences of the Child's Discussion - Xayrullayeva Marjona Xayrulla qizi (Zien Journals, 2022)
Communication is the process of informational, emotional and subjective interaction that ensures the formation, realization and manifestation of a relationship. The role of communication in the formation of a child's personality is enormous. In the process of communication, certain personal relationships are formed. In this article, you can see the formation of communication in the child, the problems and solutions that arise in it.
Keywords: communication; child; upbringing; parent